Perancangan Desain Karakter Board Game Batik Jetis Sidoarjo - Situmorang, Finka Yolanda; Romadhona, Mahimma; Sutejo, Aris (Universitas Pahlawan Tuanku Tambusai, 2024)
Sidoarjo Batik is an Indonesian cultural heritage that is rich in artistic and traditional values. However, awareness of the importance of preserving and promoting batik Jetis, especially among Sidoarjo children, still needs to be increased. This design aims to create a board game with an attractive character design for children aged 7-12 years. In this approach, the author uses qualitative research methods by collecting data through interviews, FGDs, and questionnaires to resource persons and target audiences. The results of this study provide a foundation for the design of character design in board games. The three main characters designed will serve as guides in the game and as supporting elements in the design of board game components. Hopefully, through this board game, Sidoarjo children can learn and get to know batik jetis fun while maintaining and strengthening the existence of their local culture.